2013
DOI: 10.3233/ifs-2012-0628
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy risk analysis based on a geometric ranking method for generalized trapezoidal fuzzy numbers

Abstract: In this study, we present a new method for ranking generalized trapezoidal fuzzy numbers based on the incenter and inradius of a triangle. The proposed method is simple and easy to apply to real life problems. The method can also rank crisp numbers and fuzzy numbers with the same centroid point. Some comparative examples are also given to illustrate the advantages of the proposed method. Based on the proposed ranking method, we also give an application to the fuzzy risk analysis problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…The ranking result of the proposed method is similar with Sets 2 and 3 which is affected by decision makers' perspective. For Set 6, the ranking result of the proposed method is consistent with all the existing methods except [4] and [1].…”
Section: A Comparison Of the Proposed Ranking Methods With The Existinsupporting
confidence: 64%
See 3 more Smart Citations
“…The ranking result of the proposed method is similar with Sets 2 and 3 which is affected by decision makers' perspective. For Set 6, the ranking result of the proposed method is consistent with all the existing methods except [4] and [1].…”
Section: A Comparison Of the Proposed Ranking Methods With The Existinsupporting
confidence: 64%
“…The ranking result is affected by decision makers' perspective which shows that the proposed method has a strong discrimination ability. The pessimistic decision makers produce three different ranking results with is consistent with [4], [5], [14], [7], [6], [8] and [1].…”
Section: Fuzzy Risk Analysis Based On the Proposed Ranking Methodsmentioning
confidence: 61%
See 2 more Smart Citations
“…Numerous studies have indicated that fuzzy tools are becoming very popular in risk analysis problems because of the flexibility and efficiency they give to a decision maker (e.g. Chen and Chen, 2008;Akyar et al, 2013;Madhuri et al, 2014 andAlidoosti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%